Hermeneutika Sufistik al-Ghazâlî dalam Mishkât al-Anwâr - Ghozali, Mahbub (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2015)
This paper attempts to identify the character and form of interpretation al-Ghazâlî against the Koran, especially when interpreting the verses of the Koran in one of his work, Mishkât al-Anwâr. When viewed from the authority of the text and the author (interpreter), the style of the interpretation of al-Ghazâlî appears to have similarities with the concept of philosophical hermeneutics of Gadamer. But it is not so, there are significant differences between the two. If Gadamer’s model interpretation is called Philosophical Hermeneutics, then the interpretation of al-Ghazâlî style more to the Sufi Hermeneutics. In the end, this paper concluded that al-Ghazâlî’s Sufi Hermeneutics rests on two elements are simples but not smalls; rationality (al-ma‘qûl) led by entities in it like the soul (al-nafs), soul (al-rûh), heart (al-qalb), intellect (al-‘aql), and textuality (al-manqûl) the object stratified into five aspects, namely the existence of essential (wujûd dhâtî), the existence of sensory (wujûd hissî), the existence of imaginative (wujûd khayyâlî), the existence of a rational (wujûd ‘aqlî), the existence of analogical (wujûd shibhî).